2010
DOI: 10.3402/qhw.v5i3.5482
|View full text |Cite
|
Sign up to set email alerts
|

Held to ransom: Parents of self-harming adults describe their lived experience of professional care and caregivers

Abstract: The aim of the study was to discover and describe lived experiences of professional care and caregivers among parents of adults who self-harm. Narrative interviews were conducted with six parents of daughters with self-harming behaviours and analysed using a phenomenological hermeneutic approach. The meanings of the parents' narratives of their lived experiences of professional care and caregivers were interpreted as their being involved in ‘limit situations’ comparable to hostage dramas. Several meaningful th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…There is also debate as to what specific behaviours constitute as self‐harm. The most commonly referenced methods of self‐harm are scratching, burning and cutting (Grenklo et al ., ; Lindgren, Astrom and Graneheim, ). Other authors have expanded the definition of self‐harm further by incorporating ingestion of a substance in excess of the prescribed or therapeutic dose, ‘ingestion of an illicit/recreational drug that was an act the individual regarded as self‐harm or ingestion of a non‐ingestible substance or object' (Hawton et al ., ).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also debate as to what specific behaviours constitute as self‐harm. The most commonly referenced methods of self‐harm are scratching, burning and cutting (Grenklo et al ., ; Lindgren, Astrom and Graneheim, ). Other authors have expanded the definition of self‐harm further by incorporating ingestion of a substance in excess of the prescribed or therapeutic dose, ‘ingestion of an illicit/recreational drug that was an act the individual regarded as self‐harm or ingestion of a non‐ingestible substance or object' (Hawton et al ., ).…”
Section: Contextmentioning
confidence: 99%
“…Lindgren, Astrom and Graneheim () explored this phenomenon from the perspective of the parent of a self‐harming adult in the context of parents' experience of their daughters receiving professional care. Findings indicated that participants felt accused by professionals for having excessively high demands on their daughters, but also feeling invisible when the caretaking role was taken from them and placed in the healthcare system.…”
Section: Overview Of Key Findingsmentioning
confidence: 99%
“…Lindgren, Sture, & Graneheim, 2010;Neander & Skott, 2006). A significant theme within some studies of service user experience of embedded counselling has been anger in relation to neglectful, disrespectful or abusive responses of practitioners (McLean & Flynn, 2013;O'Brien, Rose, Campbell, & Weller, 2011).…”
Section: Issues Associated With the Challenge Of Responding To Expresmentioning
confidence: 99%
“…A significant theme within some studies of service user experience of embedded counselling has been anger in relation to neglectful, disrespectful or abusive responses of practitioners (McLean & Flynn, 2013;O'Brien, Rose, Campbell, & Weller, 2011). For example, in one Swedish study, parents of young people receiving mental health treatment described themselves as being blamed and emotionally "held to ransom" by care workers (Lindgren et al, 2010). In contrast, qualitative interviews carried out by Neander and Skott (2006) identified exceptional examples of life-changing care and support provided by practitioners of embedded counselling, including instances in which long-standing negative patterns of child behaviour, such as disruptive behaviour in nursery school, were wholly resolved.…”
Section: Issues Associated With the Challenge Of Responding To Expresmentioning
confidence: 99%
“…, Lindgren et al . ). Many experience themselves as being alone in the support that they provide and they often feel stigmatised (Clarke & Winsor ).…”
Section: Introductionmentioning
confidence: 97%